The prevalence of cardiovascular diseases, chronic kidney disease, and obesity in patients with type 2 diabetes mellitus and the description of concurrent treatments: A two-center retrospective cross-sectional study in Saudi Arabia - Omar A. Alshaya; Ghazwa B. Korayem; Munirah Alghwainm; Wed Alyami; Albandari Alotaibi; Majed S. Alyami; Omar A. Almohammed (Elsevier, 2024)
Background: Atherosclerotic cardiovascular disease (ASCVD), heart failure (HF), chronic kidney disease (CKD), and obesity are associated with increased morbidity and mortality in patients with type 2 diabetes mellitus (T2DM). Nonetheless, their prevalence among patients with T2DM in Saudi Arabia (SA) remains unknown. As current guidelines recommend, these comorbidities require adding certain antidiabetic agents with cardiorenal benefits. However, the prescribers' adherence to these recommendations remains unclear. Methods: A two-center retrospective cross-sectional study was conducted including adult patients (≥18 years) with T2DM admitted to hospital or seen at outpatient clinics between January and December 2020. Patients were classified into two groups based on the presence or absence of ASCVD. Patients with no prior ASCVD history were further classified based on the 10-year ASCVD risk estimation. Endpoints of interest included the prevalence of ASCVD, HF, CKD, and obesity in patients with T2DM. We also evaluated the characteristics of the utilized antidiabetic agents, statin, and aspirin therapies.. Results: Of the 1,218 included patients with T2DM, the majority were female (57.0 %), and aged 45-64 years (53.0 %) with a mean age of 59.3 ± 13.1 years. Hypertension and dyslipidemia were the most prevalent comorbidities (67.7 % and 69.0 %, respectively). Among all patients, 18.6 % had an established ASCVD and the prevalence of HF, CKD, and obesity were 5.1 %, 8.7 %, and 58.3 %, respectively. The most common types of ASCVD witnessed were revascularization (42.3 %), myocardial infarction (36.6 %), and stroke (33.9 %); with an increased prevalence of ASCVD as the age increases (52.8 % at age ≥ 65 years). In the non‐ASCVD group, the 10-year ASCVD risk was intermediate or high in 62.7 % of these patients. The rates of utilization of guidelines-recommended therapies were 83.6 % for metformin, 9.4 % for GLP-1 RA, 10.8 % for SGLT2i, 35.2 % for aspirin alone or in combination with clopidogrel, and 79.7 % for statin therapy. Conclusions: ASCVD, HF, CKD, and obesity are common complications in patients with T2DM in SA, with low overall utilization of the recommended guidelines-recommended medical therapies. Multimodal strategies should be utilized to assess T2DM and its complications, and to improve prescribers' adherence to guidelines-recommended therapies.